Psychological status and well being among emergency medical officers in hospitals in Malaysia - Yahaya, Siti Nasrina (2017)
Health is defined is a state of complete physical, mental and social wellbeing and not merely the absence of disease or infirmity (Callahan, 1973). As applied to any occupation, an ideal job is likely to be the one which can promote career satisfaction, and at the same time has appropriate pressures on the employee’s abilities and resources. Giving autonomy, providing training in communication and management skills also are found to be important in maintaining satisfaction and enhancement of career (Ramirez et al., 1996). Across the professions, healthcare workers has been identified to be one of the most striking profession contributing to the prevalence of job dissatisfaction and work related emotional disturbances. The modern medical workplace, such as emergency department is a complex environment and they response to it vary greatly. Overcrowding with resource scarcity (Rondeau et al., 2005) leads to patient’s dissatisfaction, constant exposure to noise pollutants(ringing phones, beeping monitors, slamming doors) leads to unknowingly accumulated stress among workers (Tijunelis et al., 2005) and predisposed to violence from the patients or family members lead to feeling unsafe and job related stress (Gates et al., 2006) despite the necessity of providing essential care for them. The demand of multitasking and continuous interruption due to dynamic changes of the treated patients are common and contribute to significant disturbances of concentration and mental exhaustion (Chisholm et al., 2000). Depression is term as a mood disorder characterized by sadness, lack of interest in daily activities, inability to concentrate, disturbances in appetite and sleeping patterns (Ingram, 2012). The prevalence of depression in Malaysia is estimated from 6.3% to 13.9% (Mukhtar and PS Oei, 2011), whereas it was reported as 10.3% by Maideen et al. (2015). As for the medical students in Malaysia, the prevalence of depression reported was 37.2%by Shamsuddin et al. (2013). In a study conducted in Sheffield, the prevalence of depression among house officers were reported as 28% (Firth-Cozens, 1987), whereas in Kota Kinabalu, Malaysia it was reported as 42.9% (Shahruddin et al., 2016). As for the emergency residents, it was reported as 12.1% by Katz et al. (2006), whereas the mean score for emergency residents were found to be higher in terms of depersonalization due to depression (Michels et al., 2003). Contradicting to this, a study among Canadian family medicine residents reported that the prevalence of depression was 20% (Earle and Kelly, 2005), which is higher as compared to the emergency residents.